Second life. More than advertising a video game (Journal of Parents and Teachers, 2014)
The following article deals with the analysis of the publicity’s characteristics that they are around the videogame’s world. In addition, it offers some activities to analyze and discover what their secret messages are.
Keywords: Education; videogames; publicity; students; messages; client.